Evaluation of factors related to overdose in patients with impaired consciousness who are transported by emergency medical services: an age-specific research - Kazuki Nagashima (Journal of Pharmaceutical Health Care and Sciences, 2021)
Abstract Background Drug overdose accounts for most of the admissions to the emergency department. Prescription drugs, most of which are psychotropic medications, are often misused for drug overdose. The purpose of this study was to investigate the association between overdose in patients transported with disorders of consciousness and psychotropic medications administered prior to transport, so as to enable quick differentiation of drug overdose patients from patients with disorders of consciousness. Methods We evaluated 222 patients transported to the Advanced Critical Care Center of Teikyo University Hospital due to disorders of consciousness. The patients were categorized into two groups: overdose group (n = 128) and control group with other disorders of consciousness (n = 94). Logistic regression models were used to assess the association between disorders of consciousness due to drug overdose and psychotropic drugs prescribed before emergency transportation based on sex and age. Results According to multivariate logistic regression analysis, only female sex (odds ratio [OR] 4.54, 95% confidence interval [CI] 2.43–8.05, P < 0.0001) was associated with overall overdose. Results from the univariate logistic regression analysis showed that in the group of patients aged 40–50 years, female sex (OR 4.36, 95% CI; 1.54–12.4, P = 0.006) and the use of psychotropic drugs (OR 5.05, 95% CI; 1.75–14.6, P = 0.003), benzodiazepines (OR 4.64, 95% CI; 1.61–13.4, P < 0.05), antidepressants (OR 11.4, 95% CI; 2.35–55.8, P = 0.003), and anticonvulsants (OR 4.46, 95% CI; 1.11–17.9, P = 0.035) were associated with overdose. According to multivariate logistic regression analysis, female sex (OR 4.44, 95% CI; 1.37–14.3, P = 0.013) and antidepressants (OR 7.95, 95% CI; 1.21–52.1, P = 0.031) were associated with overdose patients aged 40–50 years. Conclusions As a reference in distinguishing overdose in women in their 40s and 50s who present with impaired consciousness, attention may need to be paid to the type of psychotropic drug used, especially antidepressants.